Between Basketball and Politics: Lithuania and Lithuanians in the Russian Media of 2010–2014 - Papaurėlytė-Klovienė, Silvija (Acta humanitarica academiae Saulensis, 2020)
The article aims to describe a part of the content of the concept LITHUANIA in the official Russian media of 2010–2014, i.e. to discuss what image of Lithuania was created in the public discourse of Russia during the mentioned period. Based on the examples of the words Литва, литовский, литовская, литовское, литовские, литовец, литовцы selected from the texts of 2010–2014 from the periodicals part of the Russian National Corpus (http://ruscorpora.ru/new/), the most common topics covered in the texts are singled out, the information encoded in the conceptual metaphors is discussed. The focus is also on the headlines of the texts, precedent texts actualized by journalists, and allusions to the history of both countries are used to increase the impact of the texts. The purpose of the study was based on the assumption that texts about another country published in one country’s public discourse (especially if those countries have unresolved problematic issues) are likely to always have a shade of political discourse. When analysing the topics that are distant from politics, it is convenient to choose the right situation to express one’s point of view on the topics of politics as well, because the emotional reaction caused by these topics can also lead to the appropriate acceptance of politically engaged information. The journalists’ statements have a direct influence on the formation of people’s attitudes, and through attitudes also affect their behaviour.Having analysed the examples selected from the Russian media of 2010–2014, which reveal the reality of life in Lithuania, it can be concluded that in most of them the values are very clear, expressed not only on the basis of what can be subtly implicated but also by employing the straightforward lexical constructions.It is concluded that in the public discourse of Russia, i.e. in official media texts, there is a very clear tendency to create an image when presenting information about Lithuania, that it is a country of poor and oppressed people, where there is no simple order, there is no freedom of speech, and most Lithuanians are hostile to Russia and Russians. Against the background of negative information, the texts that write about basketball are an exception. In them, Lithuanian coaches working in Russia and other countries, athletes are described as authoritative specialists with exceptional knowledge of their field, professionals whose opinions must be taken into account.However, most official Russian media texts of the period 2010–2014 have a very clear statement to show hyperbolically by all possible means that Lithuania, having left the former Soviet Socialist Republics, achieved absolutely nothing, it is very bad for the people in that country, and it is now dependent on the will of politicians from Western Europe or the United States. Thus, the exit from the USSR and its demolition were completely unnecessary.
Keywords: discourse analysis; Lithuanian-Russian relations; political discourse; precedent texts; public discourse